Analisis Hubungan Gaya Hidup dengan Kejadian Hipertensi pada Pasien Dewasa di Puskesmas Bagu Kabupaten Lombok Tengah - Ningsih, Yulya; Putri , Lestari Ismawati (Gema Cendekia Institute, 2026)
Hypertension remains one of the leading non-communicable diseases contributing significantly to global morbidity and mortality, particularly in developing countries such as Indonesia. Lifestyle factors are widely recognized as major determinants influencing the occurrence of hypertension, yet evidence at the primary healthcare level is still limited in specific local contexts. This study aimed to analyze the relationship between lifestyle factors and the incidence of hypertension among adult patients at Puskesmas Bagu, Central Lombok Regency. A quantitative study with a cross-sectional design was conducted involving adult patients who visited the primary healthcare facility. Data were collected using a structured questionnaire to assess lifestyle variables, including dietary patterns, physical activity, smoking habits, and sleep patterns, while blood pressure measurements were obtained using standard clinical procedures. The sampling technique employed was purposive sampling, and data were analyzed using univariate and bivariate statistical tests to determine the association between variables. The results indicated that a significant proportion of respondents had unhealthy lifestyle behaviors, particularly in terms of high salt intake, low physical activity, and smoking habits. Statistical analysis revealed a significant relationship between lifestyle factors and the incidence of hypertension (p < 0.05), suggesting that individuals with unhealthy lifestyles were more likely to develop hypertension compared to those with healthier behaviors. These findings highlight the critical role of lifestyle modification in the prevention and management of hypertension at the primary healthcare level. Therefore, it is recommended that healthcare providers, especially nurses, strengthen health education and promote behavioral interventions targeting modifiable risk factors to reduce the burden of hypertension in the community.